Społeczne zaangażowanie firm w świetle wyników indeksu BI-NGO 2007 : Komunikowanie dla poprawy wizerunku czy na rzecz jakości podejmowanych działań? - Kozakiewicz, Maciej (Corporate Community Involvement in Context of the Results of Bingo Index 2007 : Communicating for Improving Image or Quality of Undertaken Actions?, 2009)
The author analyses the factors motivating companies to communicate their corporate community involvement (CCI) based on the analysis of the results of the newly created Bl-NGO Index. The survey was carried out in spring 2007 on a sample of five hundred companies listed on the "Lista 500" published by the daily paper Rzeczpospolita. The research was coordinated by the Institute of Partnership Business and Non-Governmental Organisations BI-NGO (a joint initiative of the Faculty of Management at the University of Lodz and a firm CSR Consulting). The survey showed the existence of a correlation between economic size of the company and the quality with which their social commitment is communicated. Methodology does not judge the scale actions with an emphasis on the quality of communication, which means that even a small firm is able to receive the maximum rating in the Index. Yet this study shows that the smaller the company's economic value, the greater the likelihood of a lower quality of the way that activities in the social field are communicated. And that regardless of the fact that the quality of communication of social activities by companies has been dynamically growing in the last period, as evidenced by the quantity of reports published by companies.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 42, s. 126-135